2012
DOI: 10.1007/s00345-012-0971-5
|View full text |Cite
|
Sign up to set email alerts
|

Female sex is an independent risk factor for reduced overall survival in bladder cancer patients treated by transurethral resection and radio- or radiochemotherapy

Abstract: Female sex is an independent prognostic factor for reduced OS and CSS in bladder cancer patients treated by TURBT and RT or RCT. These data are in agreement with those reported for OS after radical cystectomy in muscle-invasive bladder cancers. Therefore, further studies are strongly warranted to obtain more information about molecular differences regarding sex-specific carcinogenesis in bladder cancer and about possible therapeutic considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…In non-muscle-invasive bladder cancer, Kluth et al [14] reported that female gender was associated with a higher risk of disease recurrence. Similar findings were observed by the Club Urológico Español de Tratamiento Oncológico [15], Palou et al [16] and Keck et al [17], who demonstrated that female gender was an independent predictor of disease recurrence, progression and impaired overall survival. On the other hand, Sylvester et al [18] did not find an independent impact of gender within EORTC trials comprising roughly 2,600 patients with Ta or T1 non-muscle-invasive bladder cancer after TUR-BT.…”
Section: Discussionsupporting
confidence: 71%
“…In non-muscle-invasive bladder cancer, Kluth et al [14] reported that female gender was associated with a higher risk of disease recurrence. Similar findings were observed by the Club Urológico Español de Tratamiento Oncológico [15], Palou et al [16] and Keck et al [17], who demonstrated that female gender was an independent predictor of disease recurrence, progression and impaired overall survival. On the other hand, Sylvester et al [18] did not find an independent impact of gender within EORTC trials comprising roughly 2,600 patients with Ta or T1 non-muscle-invasive bladder cancer after TUR-BT.…”
Section: Discussionsupporting
confidence: 71%
“…In this series, the median overall survival was 5.1 years for men versus only 2.3 years for women (p = 0.045) [17]. The estimated median cancer-specific survival was 7.1 years for female versus 12.7 years for male patients [17]. …”
Section: Discussionmentioning
confidence: 99%
“…However, they present with more advanced tumours, thus explaining the observation of poor outcomes in an unmatched cohort. Keck et al analysed the impact of gender on the outcome of invasive bladder cancer managed by a multimodal bladder sparing approach in 105 female and 386 male patients [17]. In this series, the median overall survival was 5.1 years for men versus only 2.3 years for women (p = 0.045) [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burger et al [14] recognised the research gap of gender in urology and therefore analysed existing descriptions of gender effects in general oncological and uro-oncological research. Keck et al [15] evaluate sex as a possible prognostic factor in bladder cancer patients treated by transurethral resection and radio-or radiochemotherapy. Brookman-May et al [16] demonstrate the importance of gender differences in clinical and pathological features as well as the outcomes of patients with renal cell carcinoma after surgery.…”
mentioning
confidence: 99%